HUBUNGAN PENDIDIKAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MEUREUBO TAHUN 2024 - Salmaza; Iskandar, Wardah; Eka Putri, Suci; Muliadi, Teuku (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to look at the relationship between education, knowledge and family support with exclusive breastfeeding behavior in the working area of ​​the Meureubo Health Center in 2024. This research method uses a quantitative approach with a cross sectional design. The population in this study were all mothers who had babies aged 6-12 months. Respondents in the study were 123 who had babies aged 6-12 months. The instrument used was a questionnaire. Data analysis used chi-square. The results of the research show that there is a significant relationship between education and exclusive breastfeeding behavior in the Meurebo Community Health Center working area with a p value of 0.029 < 0.05. There is a significant relationship between knowledge and exclusive breastfeeding behavior in the Meurebo Community Health Center working area with a p value of 0.035 < 0 .05, There is no significant relationship between family support and exclusive breastfeeding behavior in the Meurebo Community Health Center Area with a p value of 0.730 > 0.05. The conclusion is that there is a significant relationship between education and knowledge and exclusive breastfeeding behavior in the working area of ​​the Meureubo Community Health Center. Then there is no significant relationship between family support and exclusive breastfeeding behavior in the working area of ​​the Meureubo Community Health Center.